Screening tests and biochemical markers in alcohol use disorders - Gül, Selami; Akvardar, Yıldız (Journal of Dependence, 2008)
Screening tests facilitate the alcohol use disorder diagnosis. CAGE (acronym for Cut down. Annoyed, Guilty, Eye-opener) and Alcohol Use Disorder Identification Test (AUDIT) are frequently used screeening tests. The sensitivity of Michigan Alcoholism Screening Test is lower. The validity of shorter screening tests (eg. CAGE, AUDIT) is higher. The limitation of screening tests is the necessity to rely on the memory and honesty of cases. Besides the alcohol related memory problems, denial often seen in these disorders makes these tests less reliable. Therefore biochemical markers are needed. In the past two decades carbohydrate deficient transferrin (CDT) has been most widelystudied and mosthopeful marker. Butthecomplicated test procedure, high cost and less avalibility are problems about this marker. GGT (gama glutamyltransferase) which is reported to have lower sensitivity has advantages such as the higher avalibility, low price and simple test procedure. The high specifity and suitability as a relapse marker are the most important advantages of CDT. GGT has limitations on these aspects according to CDT. The studies on the new markers for alcohol use disorders as objective indicators are going on. Beta-hexozaminidase (p-Hex) and 5-hydroxytryptophol (5-HTOL) has been proposed. Screening tests and biochemical markers are valuable for motivation enhancement in treatment, security measures in certain professions, public health and other scientific studies.